Roland Barthes at the Collège de France. - O'Meara, Lucy. (Contemporary French and Francophone Cultures Series, 2013)
A full-length account of Barthes' lecture courses given in Paris,1977-80, placing his teaching within institutional, intellectual and personal contexts. Analysing texts and recordings of the four lectures together with his 1970s output, it brings together all the strands of Barthes' activity as writer, teacher and public intellectual.